The Potential Of Antisense Oligonucleotides (ASO) Through Inhalation Based On Gold Nanoparticle (AuNP) Delivery System In Inhibiting SARS-CoV-2 Replication And Transcription - Deanasa, Raehan Satya; Afladhanti, Putri Mahirah; Syafira, Fara (SCRIPTA SCORE Scientific Medical Journal, 2022)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This virus infects the respiratory, digestive, and nervous systems with a rapid transmission and a fairly high mortality rate. However, there has been no specific therapy to treat COVID-19. Previous studies have shown that antisense oligonucleotide (ASO) has good efficacy in DNA and RNA viral infections. This literature review aims to investigate the potential of inhaled ASO based on gold nanoparticles (AuNp) delivery system in inhibiting the replication and transcription of SARS-CoV-2. Literature searching using several databases, such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria are used to eliminate the journals that does not match the criteria, thus 28 journals are obtained. The results show that ASO has the potential to inhibit the replication and transcription of the SARS-CoV-2 virus through different mechanisms by binding to the target RNA and modulating the viral protein synthesis. One form of ASO modification that is often used is LNA GapmeR. LNA GapmeR stimulates viral RNA cleavage and can be administered by inhalation with nebulized ASO solution. AuNP as an ASO delivery system through inhalation can reduce toxicity and increase ASO concentrations in reaching target cells. Therefore, ASO therapy with AuNP through inhalation needs to be considered for COVID-19 treatment. Further clinical study about the ideal delivery system and optimal dosage of ASO based AuNP via inhalation for COVID-19 are needed to investigate soon.